Progress in Ultrafast Intense Laser Science VII - Yamanouchi, Kaoru.; Yamanouchi, Kaoru.; Charalambidis, Dimitrios.; Charalambidis, Dimitrios.; Normand, Didier.; Normand, Didier. (Progress in Ultrafast Intense Laser Science ;, 2011)
The PUILS series delivers up-to-date reviews of progress in Ultrafast Intense Laser Science, a newly emerging interdisciplinary research field spanning atomic and molecular physics, molecular science, and optical science, which has been stimulated by the recent developments in ultrafast laser technologies. Each volume compiles peer-reviewed chapters authored by researchers at the forefront of each their own subfields of UILS. Every chapter begins with an overview of the topics to be discussed, so that researchers unfamiliar to the subfield, as well as graduate students, can grasp the importance and attractions of the research topic at hand; these are followed by reports of cutting-edge discoveries. This seventh volume covers a broad range of topics from this interdisciplinary research field, focusing on the ionization of atoms and molecules, ultrafast responses of protons and electrons within a molecule, molecular alignment, high-order harmonics and attosecond pulse generation, and acceleration of electrons and ions in laser plasmas.